Environmental catalysis and the chemistry of SO2 on oxide surfaces: fundamental principles for the cleavage of S-O bonds - Rodríguez, José (Ciencia, 1970)
The rational design of catalysts with a high efficiency for the destruction of SO2 (DeSOx process) is a major problem in environmental chemistry. This article presents an overview of recent studies that use synchrotron-based photoemission, x-ray near edge absorption spectroscopy, and first-principles density functional calculations to examine the interaction of SO2 with single-crystal surfaces and powders of oxides. On pure stoichiometric oxides (MgO, Al2O3, TiO2, Cr2O3, Fe2O3, NiO, CuO, ZnO, ZrO2, V2O5, MoO3, CoMoO4 and NiMoO4), SO2 reacts with the O centers to form SO3 or SO4 species that decompose at elevated temperatures. Adsorption on the metal cations occurs below 300 K and does not lead to cleavage of S-O bonds. In typical oxides, the occupied cation bands are too stable for effective bonding interactions with the LUMO of SO2. To activate an oxide for S-O bond cleavage, one has to generate occupied metal states above the valence band of the oxide. This basic requirement can be accomplished by the creation of O vacancies, alkali (Na, K, Cs) promotion, or doping with a transition metal. Metal dopants are useful for inducing the formation of O vacancies in many oxides. In addition, a dopant agent can directly introduce occupied states within the band gap of an oxide. For TMxMg1-xO systems (TM= Zn, Sn, Ni, Co, Fe, Mn, or Cr), a correlation is found between the energy position of the dopant-induced states and the ability of the mixed-metal oxide to break S-O bonds. The behavior of the CrxMg1-xO system illustrates a fundamental principle for the design of DeSOx catalyst.